PENGARUH RASIO PEMENUHAN KECUKUPAN MODAL MINIMUM, BOPO, LDR DAN SIZE TERHADAP NET INTEREST MARGIN PADA PERUSAHAAN BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 â 2015 - Agung Nugrahaning Widi, 11.05.52.0109; Aini, Nur (Students Journal of Accounting and Banking, 2017)
The purpose of this study was to analyze the Influence Fulfillment Minimum Capital Adequacy, BOPO, LDR, and the size of the net interest margin in the banking companies listed in Indonesia Stock Exchange 2013-2015 period.Â This study uses popullasi all banks listed on the Stock Exchange in the year 2013-2015. The sampling technique used purposive sampling. The analytical tool used is a linear regression analysis. The results of the analysis concludes known PKMM postifif effect no significant effect on the net interest margin. BOPO a significant negative effect on the net interest margin. This means that the higher the ROA, the companys net interest margin will decline. LDR or (Loan Deposit Ratio) had no significant positive effect on the NIM. Or size (size of the company) had no significant positive effect on the NIM.Keywords: Effects of The Minimum Capital Adequacy Compliance, BOPO, LDR, Size and The Net Interest Margin